The making of the King James Bible [videorecording (DVD)]. - Griffith, Jerry, 1958- (Gateway Films (Vision Video), 2010)
The year 2011 marks the 400th anniversary of the creation of the King James Bible, arguably the greatest piece of English Literature ever produced. King James had an uncanny love of beautiful things, including language to stir the soul. With several English translations in use across the Kingdom, the Puritan leader John Rainolds took his opportunity to suggest that a new, more accurate translation was needed for the people.